2015
DOI: 10.1103/physrevb.92.174524
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and Pauli limiting effects in heavily dopedBa0.05K0.95Fe2As2

Abstract: We investigated the thermodynamic properties of the Fe-based lightly-disordered superconductor Ba0.05K0.95Fe2As2 in external magnetic field H applied along the FeAs layers (H||ab planes). The superconducting (SC) transition temperature for this doping level is Tc = 6.6 K. Our analysis of the specific heat C(T, H) measured for T < Tc implies a sign change of the superconducting order parameter across different Fermi pockets. We provide experimental evidence for the three components superconducting order paramet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…The behavior of heat capacity observed here was found experimentally in many multi-band materials like iron-based superconductors from 11 [71,72], 111 [73][74][75], or 122 family [52,[76][77][78][79][80][81][82][83][84][85][86][87], MgB 2 -classical two band superconductor [88] and many others (e.g., 2H-Pd x TaSe 2 [89], Lu 2 Fe 3 Si 5 [90] or NbS 2 [91]). One needs to stress that the unconventional superconductors (with the gap symmetry other than s-wave) is characterized by a different dependence of C vs. T/T c .…”
Section: Specific Heatsupporting
confidence: 62%
“…The behavior of heat capacity observed here was found experimentally in many multi-band materials like iron-based superconductors from 11 [71,72], 111 [73][74][75], or 122 family [52,[76][77][78][79][80][81][82][83][84][85][86][87], MgB 2 -classical two band superconductor [88] and many others (e.g., 2H-Pd x TaSe 2 [89], Lu 2 Fe 3 Si 5 [90] or NbS 2 [91]). One needs to stress that the unconventional superconductors (with the gap symmetry other than s-wave) is characterized by a different dependence of C vs. T/T c .…”
Section: Specific Heatsupporting
confidence: 62%
“…Generally speaking, the anisotropy parameter γ of the FeSCs was found to be much smaller than that of the cuprates and the theoretical calculations. 8,[10][11][12][13][14][15][16] Although the Pauli-limit effects have been taken into account in well understanding the low temperature behaviors of H c2 , [17][18][19] the nature of such small value of anisotropy parameter γ of FeScs remains unclear in the vicinity of superconducting (SC) transition temperature T c . Interestingly, it has been found that the values of ln(γ 2 ) is linearly proportional to the distance d of adjacent conducting layers for both the cuprates supeconductors and FeSCs, 8,11 which is understandable since a thicker insulating block layer weakens the interlayer hybridization, as a result the anisotropy will be enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Deviations can be particularly pronounced when magnetic field is aligned parallel to the conducting plane, so that orbital upper critical fields can become higher than paramagnetic limit [11]. Crossover between the orbital and paramagnetic limiting mechanisms leads to a difference in the shape of the H c2 (T ) line, which was noted in KFe 2 As 2 [9,12] and nearby hole-overdoped Ba 1−x K x Fe 2 As 2 compositions [13,14]. The importance of the paramagnetic limiting effects was also suggested by the observation of the first order transition at H ab c2 (T ) line at low temperatures in thermal expansion and magnetostriction measurements in KFe 2 As 2 [15], small angle neutron scattering [16] and anomalous hysteresis in field-sweep resistivity measurements [13].…”
Section: Introductionmentioning
confidence: 99%